Enhancing Income of Farmers using Group Approaches - D.K. Singh, S.B. Agrawal , D.P. Sharma, D. Singh, S.K.Pandey (Indian Journal of Extension Education, 2022)
The group dynamics refers to a set techniques such as role playing buzz sessions, observation and feedback of group process and group decision which have been employed during the post decade. BIGs is a group of rural poor Farmers/farm women who have interest and volunteered to organize themselves into a group for eradication of poverty of the members. To make the livelihood sustainable the formation of BIG has been planned as the Brewing Interest Group is the body of interested farmers. This model assessed by Krishi Vigyan Kendra, Jabalpur in this On Farm Trials and selected two groups (Seed Production of Pea and Lac Production) comprises of 20 members in each group selected for assessment. The performance of the technology taken by number of ideas broad casted, response analysis, number of emerging on the basis of response analysis, Brewing Interest Group linked with financial institution and over impact of the livelihood improvement. Both group earned the profit through this dynamic approach some of Rs.81,000 profit and Rs. 21,415 respectively. Since problem was identified low household income due to unorganized agri-base entrepreneurs however this group dynamics approach through Brewing Interest Group over come two this problem which is our ultimate outcomes “Entrepreneurship development through group approaches”.